PROTOTYPE OF FALL MOTION DETECTION DEVICE FOR THE ELDERLY USING THE MPU6050 ACCELEROMETER SENSOR BASED ON THE INTERNET OF THINGS - Ade Ayu Rahmawati; Rio Rahagung; Fajar Gumilang (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2025)
This research aims to create a fall motion detector prototype that can be used by the elderly using the MPU6050 accelerometer sensor. By utilizing IoT technology, this fall detector device can provide automatic notifications via the Telegram application or short messages when a fall event is detected. This system works with an automatic system that utilizes ESP8266 as a microcontroller and Telegram as an IOT-based monitoring dashboard and sensors that work to provide input values ​​to the microcontroller. The IoT-based fall motion detector prototype has successfully sent a fall warning through the sound of a buzzer as an alarm and also notifications from Telegram. The author made a safe threshold at a value of 1.5 G because when it is detected that the value is above the threshold, the device will automatically detect if there is a shock and fall.